HUBUNGAN ANTARA KEBIASAAN CARA MEMASAK SAYURAN DAN KADAR CHOLINESTERASE TERHADAP STATUS HORMON THYROID WANITA USIA SUBUR DI DAERAH GONDOK ENDEMIK - Sukati Saidin; Nurdin .; Hardinsyah .; Ikeu Tanziha (PERSATUAN AHLI GIZI INDONESIA, 2008)
THE ASSOCIATION BETWEEN FREE THYROXINE AND VEGETABLES COOKING AND SERUM CHOLINESTERASE OF CHILD BEARING AGE WOMEN IN ENDEMIC GOITRE AREAPesticides, a goitrogenic pollutant, strongly bind iodine to make a complex substance which iodinecan not optimally be utilized and leads to impair thyroxine hormone production. Farmers in Pakissub district of Magelang district often put pesticides of organophosphate and carbamate groups toincrease vegetables yield. The retained pesticides in the foods can be minimized by cooking. Todetermine the association between free thyroxine sera and vegetable cooking and cholinesterasesera. A cross-sectional study design was applied to 205 of child bearing age women (CBAW) of 17– 45 years of age in Pakis sub district of Magelang District, Central Java. Vegetable in whichpesticide may persist were cooked in two ways, namely were boiled and tumis (stir fried). Bloodspicement were drawn for fT4 and cholinesterase axamination. It was indicated that serum FT4 of68,3 % of CBAW were normal, while 31,7 % of them were low and 5.1% of CBAW with low serumCHE. There was a significant association between the way of cooking , status of serum CHE andcontraceptive use of family planning with to status of serum FT4. The child bearing age womenthat consume vegetables cooked by “tumis” (cooking stir fried) having higher risk of low serum freethyroxin status, 2,5 times than that of by boiling. CBAW with low cholinesterase enzyme (CHE)having lower risk of low serum free thyroxin hormone status (FT4), 10 times than that of withnormal CHE. CBAW with hormonal contraception having higher risk of low serum FT4, 0,50times than that usage non hormonal contraception. In order to minimize pesticide residuesretained in vegetables, it should be cooked by boilingKey words:iodine status,pesticide, cholinesterase, cooking stir fried, child bearing age women,thyroxine status,endemic goiter